Teknik Self-Regulated Learning untuk Meningkatkan Kemampuan Self-Regulated Learning dan Kemandirian Belajar Siswa dalam Situasi Belajar Online Covid 19 - Muhamad Khoirudin; Eko Darminto; Retno Tri Hariastuti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The ability of self-regulated learning and independent learning is needed for humans throughout their lives. However, the students of SMP Sunan Ampel Porong do not yet have optimal learning independence. This study aims to improve self-regulated learning abilities and increase the learning independence of Sunan Ampel Porong Junior High School students in online learning situations during the COVID-19 pandemic, through the application of self-regulated learning techniques. This research uses experimental research, the method used is quasi-experimental research design with non-equivalent control group design. The results of this study are (1) The level of effectiveness of self-regulated learning techniques to improve the ability of self-regulated learning and learning independence of students is in the high category. The use of self-regulated learning techniques is quite effective in increasing self-regulated learning abilities and independent learning, (2) the level of students' self-regulated learning abilities increases significantly after being guided through self-regulated learning techniques which are in the high category. There was a significant increase in the results of the self-regulated learning ability of students in the experimental group or those given self-regulated learning techniques, and (3) the level of learning independence of students increased significantly after being guided through self-regulated learning techniques was in the high category. There was a significant increase in the learning independence result scores of students in the experimental group or those given self-regulated learning techniques. Kemampuan self regulated learning dan kemandirian belajar diperlukan bagi manusia sepanjang hidupnya. Namun, peserta didik SMP Sunan Ampel Porong belum memiliki kemandirian belajar optimal. Penelitian ini bertujuan untuk meningkatkan kemampuan self regulated learning dan meningkatkan kemandirian belajar peserta didik SMP Sunan Ampel Porong dalam situasi pembelajaran daring di masa pandemi covid-19, melalui penerapan Teknik self regulated learning. Penelitian ini menggunakan jenis penelitian eksperimen, metode yang digunakan adalah quasi eksperimen dengan rancangan penelitian non-equivalent control group design. Hasil penelitian ini adalah (1) Tingkat keefektifan teknik self-regulated learning untuk meningkatkan kemampuan self-regulated learning dan kemandirian belajar peserta didik berada pada kategori tinggi. Penggunaan teknik self regulated learning cukup efektif untuk meningkatkan kemampuan self regulated learning dan kemandirian belajar, (2) tingkat kemampuan self-regulated learning peserta didik meningkat secara signifikan setelah dibimbing melalui teknik self-regulated learning berada pada kategori tinggi. Terdapat peningkatan secara signifikan pada skor hasil kemampuan self regulated learning peserta didik kelompok eksperimen atau yang diberikan teknik self regulated learning, dan (3) tingkat kemandirian belajar peserta didik meningkat secara signifikan setelah dibimbing melalui teknik self-regulated learning berada pada kategori tinggi. Terdapat peningkatan secara signifikan pada skor hasil kemandirian belajar peserta didik kelompok eksperimen atau yang diberikan teknik self regulated learning.